The The Study on Age-Friendly Environments for an Improvement of Quality of Life for Elderly, Asian Mega City, Thailand - P. Iamtrakul; S. Chayphong; J. Klaylee (Lowland Technology International, 2019)
With the global trends of urbanization and aging population, more focus about the design of age-friendly environments to improve quality of life for our residents aged of 60 years and more is increasing. The pursuit of healthy, productive, and purposeful aging must become a priority for all communities, especially in Asian megacity, Thailand. In order to enable living environment for older people as a resource for their families, communities and economies, the complex infrastructure and social context must be unfolded. Thus, this study attempted to understand the health related problem of age groups among difference life styles and neighborhood characteristics toward the appropriate recommendation of an age-friendly city by conducting the site investigation together with questionnaire survey. The total 1,000 sets of older people were interviewed by working closely with authorities from Banpaew district of Samutsakorn Province, Thailand. By adopt the technique of focus groups among caregivers and service providers in the public, voluntary and private sectors, the in-depth interview could be executed and comprehended. The results from the focus groups led to a guideline development for age-friendly city improvement. Finally, an ultimate aim of recommendation for longevity urban environment could be promoted to encourage active ageing by optimizing opportunities for health, participation and security in order to enhance quality of life.